Analysis the Use of E-Book in Science Education: A Systematic Literature Review - Fadilah Alfiani; Diana Rochintaniawati; Nanang Winarno; Sjaeful Anwar; Jefelson M. Paltep (Jurnal Pendidikan Sains Indonesia, 2026)
The advancement of digital technology has brought significant transformation to science education, which is often regarded as complex and abstract. One rapidly growing learning medium is the e-book. However, despite the increasing number of studies on the use of e-books in education, there has been no systematic review specifically analyzing the characteristics of the literature and the recommendations made by researchers regarding their use in the context of science education. This study aims to analyze 40 articles from scopus-indexed international journals published between 2017 and 2025 concerning the use of e-books in science education. The method employed is a systematic literature review (SLR) following the PRISMA guidelines. The results indicate that the majority of the articles are derived from quantitative journals, focus on the university level, and are dominated by science and biology content. Additionally, previous research suggestions are categorized into five main areas: sample characteristics, intervention duration, learning methods, context/topic of study, and methodological design. The findings provide a comprehensive mapping of research trends related to e-books in science education and can serve as a foundation for the development of media, curriculum, and future research that is more innovative, relevant, and sustainable in the digital era